Risk Factors of Stunting in Children Aged 1-5 Years at Wire Primary Health Care, Tuban Regency, East Java - Puspitasari, Prastiwi Novia; Irwanto, Irwanto; Adi, Annis Catur (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background : Stunting is the most common malnutrition condition found in children around the world. Many factors can affect toddler nutritional status and cause stunting in them. They include genetic factors, family socioeconomic level, medical history and feeding practices. The present study aims to determine the impact of those factors on stunting incidence in children aged 1-5 years.Subjects and Method: The data was analyzed using cross-sectional approach with 109 mothers with children aged 1-5 years. Data collection was carried out by the means of direct interview using a questionnaire that has been validated for contents and toddler and parent height measurement.Results: The results showed that father and mother height, dietary diversity and fish consumption influenced stunting incidence in children aged 1-5 years. The mothers